Spectrum of changes in placenta in toxemia of pregnancy - Aparna Narasimha; D S Vasudeva (Indian Journal of Pathology and Microbiology, 2011)
Background: Toxemia of pregnancy is the leading cause of maternal mortality and is an important factor in fetal wastage. The incidence is high in developing countries with malnutrition, hypoproteinemia, and poor obstetric facilities. Objectives: The present study was undertaken to analyze placental changes in the preeclampsia-eclampsia syndrome with a view to assess the significance of villous abnormalities by histopathological methods because these changes serve as a guide to the duration and severity of disease. Gross abnormalities noted were the placental infarcts, retroplacental hematoma, and calcification. Results: The striking villous abnormalities observed in the study group were cytotrophoblastic proliferation (86%), thickening of the villous basement membranes (95.23%), increase in syncytial knots (90.4%), villous stromal fibrosis (92%), fibrinoid necrosis (97.82%), endarteritis obliterans (53.96%), decreased villous vascularity, and paucity of vasculosyncytial membranes (93.65%). Conclusions: The gross abnormalities and villous lesions in the preeclampsia (P < 0.001) and eclampsia syndrome (P < 0.05) were significant.